P1038NEPHROPROTECTIVE EFFECT OF SGLT2 INHIBITORS DURING FIRST YEAR OF TREATMENT. (6th June 2020) - Almeida, Catarina; Silva, Leonor; Costa, Tiago; Lopes, Daniela; Andrade, Luís
Abstract: Background and Aims: SGLT2 inhibitors, the most recent glucose-lowering oral agents, have the potential to exert nephroprotection not only through improving glycemic control but also through glucose-independent effects. Recent studies demonstrate this effect with decreased albuminuria and lowering the progression of chronic kidney disease. The aim of our study was to evaluate the effect of iSGLT2 on glomerular filtration rate and albuminuria during the first year of treatment. Method: This was a retrospective cross-sectional study that included patients diagnosed with DM2 and treated with an iSGLT2 during 1 year in a Diabetic Clinic. Demographic and clinical variables were collected, including HbA1c, disease duration and cardiovascular risk factors (CVRF). Patient glucose-control therapy as well as RAAS inhibitor drugs were gathered. The estimated Glomerular Filtration Rate (eGFR) by the formula CKD-EPI and albuminuria, using the urinary albumin-to-creatinine ratio, were evaluated at the iSGLT2 introduction date and at 3, 6, 9 and 12 months of treatment. Results: We analyzed 208 patients, 53.8% male, mean age 65.5 years, median baseline HbA1c 8.4% and median duration of DM2 14 years. Of all patients, 94.2% had at least 1 CVRF, 71.6% were hypertensive, 83.2% had dyslipidemia, 48.1% were obese, and 25.2% had past/current smoking habits. Regarding glucose-control therapy, only 20.2% were treated with one oral drug class and the remaining with 2 or more classes, with 81.7% of the patients receiving metformin and 51.4% being on insulin therapy. Overall, 63.5% of patients received dapaglifozin therapy and 36.5% empaglifozin. Also, 56.3% were on a RAAS inhibitor. Regarding eGFR, 15.6% patients had an eGFR between 30 and 60 and 84.4% patients had an eGFR greater than 60 ml/min/1.73m2. As for albuminuria, 37 patients had normal albuminuria (<30mg/g), 18 patients had moderate albuminuria (30-300mg/g) and 6 patients had severe albuminuria (>300mg/g). In 12 months, there was a significant reduction in HbA1c (mean variation 0.5%) (p<0.001). Evaluating eGFR throughout the year, a decrease was observed in the first 6 months from an average of 81.6 to 78.5 ml/min/1.73m2 (p=0, 001). Although on the second semester, there was an increase in eGFR to 83.4 ml/min/1.73m2 (p<0.001). These were similar in patints treated with dapagliflozin and empagliflozin. In patients with eGFR <60ml/min at the admission, there was an increase in eGFR from 49.6 to 53.4ml/min/1.73m2 after one year of treatment (p=0, 260). A decrease in albuminuria levels was observed in the first year of iSGLT2 use, either in the case of moderate albuminuria (initial median of 80.52mg/g to 54.88mg/g) (p=0, 758) or severe albuminuria (initial mean 650.40mg/g to 420.28mg/g) (p=0, 213). Conclusion: This data shows that after an initial reduction in eGFR during the first 6 months of treatment, the use of iSGLT2 after one year improved the eGFR, promoting a nephroprotective effect in type 2 diabetic patients.